Systemic and local antibody responses to gastric Campylobacter pyloridis in non-ulcer dyspepsia. Issue 6 (June 1986) - Rathbone, B J; Wyatt, J I; Worsley, B W; Shires, S E; Trejdosiewicz, L K; Heatley, R V; Losowsky, M S
Abstract : Antibody titres to Campylobacter pyloridis in serum and gastric juice were estimated by an enzyme linked immunosorbent assay (ELISA) to whole organisms obtained from bacterial culture in 39 patients with non-ulcer dyspepsia. Whereas 20 of the 21 patients with chronic gastritis had gastric C pyloridis, 17 patients with no C pyloridis had normal histology in the gastric antrum and body. Significantly raised serum IgG and IgA antibody titres to C pyloridis were found in colonised patients with gastritis. Patients with raised IgG antibody to C pyloridis were also shown to have significantly raised titres to other Campylobacter species, suggesting antigenic cross reactivity. Gastric juice antibodies were also studied and IgA titres to C pyloridis were detected in a proportion of patients with gastritis, together with low levels of IgM, but no IgG.